Is disease a threat to identity? A systematic review of parkinson's disease and personal identity - Ashima Nehra; Rhythm Makkar; Rajesh Kumar Singh; Roopa Rajan; Maroof Ahmad Khan; Achal Kumar Srivastava (Wolters Kluwer Medknow Publications, 2023)
Introduction: Parkinson's disease (PD) is a neurological condition that impacts the physical and psychological functioning of the patients. The physical and cognitive changes come with social stigma and threats to roles previously associated with their identities. Objectives: The current paper attempts to study the influence of the disease on the personal identity of the patients. Methods: A systematic review was done on PD and personal identity following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. The Consolidated Criteria for Reporting Qualitative Research checklist was used to assess the quality of the papers. The selected papers were synthesized to understand the relationship between PD and personal identity. Results: The emerging themes were: (1) dissociation of old personal identity: (1.1) Influence of physical symptoms, (1.2) influence of society and stigma, and (1.3) threats to roles associated with identity and (2) changing family dynamics. A Model of Personal, Family, and Disease Dynamics was also developed based on clinical first-hand experience with the patients and the review. Conclusion: The personal identity of the PD patients shifts drastically as a result of their physical and psychosocial experiences. This also results in changed family dynamics, with the patient feeling sidelined due to loss of control and responsibilities in the family.